What influences young doctors in their decision-making about general practice as a possible career? A qualitative study. Issue 1 (2nd January 2020) - Harris, Michael; Wainwright, David; Wainwright, Elaine
ABSTRACT: Background : Recruitment to General Practitioner (GP) training programmes in the United Kingdom is poor. Colleagues' negative comments about general practice could contribute to this. Aim : To investigate what influences Foundation Year 2 (FY2) doctors in their decisions to choose general practice as a career, and how colleagues' comments about GPs might affect those decisions. Design and Setting : A qualitative study in Southwest England. Method : Thematic analysis of interviews with FY2 doctors. Results : Twenty-four doctors participated. They thought that GPs worked hard and had very varied clinical work. The effect on their career choice depended on their personalities. GP placement experiences significantly influenced their career intentions. The loneliness of working in general practice was a key concern. FY2 doctors thought colleagues' criticisms of GPs did not reflect reality and were outdated. 'Banter' had little effect on career choices. Conclusion : Person-specialty fit and FY2 doctors' experiences of GP work have a significant effect on career choices. Loneliness in their GP work placements is a particular problem that should be addressed. While colleagues' derogatory comments about GPs may affect medical students' views on their career choices, they appear to have little effect on the career decision-making of qualified doctors. Abbreviations : CMT: Core Medical Training; FY2: Foundation Year 2; GP: general practitioner; NHS: National Health Service; UK: United Kingdom